Structure of the concept of «musical patriotic culture of schoolchildren» - Ol’ga V. Yusupova; Galina N. Maximenko (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
The relevance of the study is due to the increased attention to the patriotic education of the younger generation and the search for new forms and means of its implementation. The paper substantiates the need to introduce the concept of “musical patriotic culture of schoolchildren” and proposes its structure. Music adds a bright emotional component to develop a sense of patriotism in schoolchildren. The systematic introduction of elements of musical culture, reflecting the history of the country, into the targeted educational process, introducing schoolchildren to musical national traditions enriches and makes the process of patriotic education of schoolchildren more effective.